2019
DOI: 10.1002/adfm.201901171
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Indoor Organic Photovoltaics with Spectrally Matched Fluorinated Phenylene‐Alkoxybenzothiadiazole‐Based Wide Bandgap Polymers

Abstract: The unique electro‐optical features of organic photovoltaics (OPVs) have led to their use in applications that focus on indoor energy harvesters. Various adoptable photoactive materials with distinct spectral absorption windows offer enormous potential for their use under various indoor light sources. An in‐depth study on the performance optimization of indoor OPVs is conducted using various photoactive materials with different spectral absorption ranges. Among the materials, the fluorinated phenylene‐alkoxybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 42 publications
0
67
0
Order By: Relevance
“…In the previous work, we have demonstrated that the vacuum‐deposited OPV can exhibit a PCE close to 16% under a TLD‐840 fluorescent lamp (800 lux; 0.232 mW cm −2 ), [ 73 ] which might indicate that new energy‐harvesting technology can convert the environmental or sunlight energy efficiently to drive low‐power‐consumption electronics. [ 74 ] Several materials and systems, such as OPVs, [ 53,54,75 ] dye‐sensitized solar cells, [ 76 ] polymer solar cells, [ 77–79 ] and perovskite PVs [ 80,81 ] have been used to achieve high‐efficiency self‐sustainable power in the past 3 years. [ 82 ] Here, we propose that the TPV module developed in this work can directly charge a homemade LiFePO 4 (LFP) battery (CR2032 coin cell; Figure S13, Supporting Information) with a capacity of 0.58 mAh under the sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous work, we have demonstrated that the vacuum‐deposited OPV can exhibit a PCE close to 16% under a TLD‐840 fluorescent lamp (800 lux; 0.232 mW cm −2 ), [ 73 ] which might indicate that new energy‐harvesting technology can convert the environmental or sunlight energy efficiently to drive low‐power‐consumption electronics. [ 74 ] Several materials and systems, such as OPVs, [ 53,54,75 ] dye‐sensitized solar cells, [ 76 ] polymer solar cells, [ 77–79 ] and perovskite PVs [ 80,81 ] have been used to achieve high‐efficiency self‐sustainable power in the past 3 years. [ 82 ] Here, we propose that the TPV module developed in this work can directly charge a homemade LiFePO 4 (LFP) battery (CR2032 coin cell; Figure S13, Supporting Information) with a capacity of 0.58 mAh under the sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…1a and Table 1). 27 However, for fullerene-based blend systems, there is limited potential to further enhance the V oc value since the energy level of the fullerene acceptor cannot easily be adjusted and only the energy level of the polymer donor can be tuned. Nonfullerene acceptors (NFAs), on the other hand, offer more opportunities to deliver higher V oc due to more adjustable properties of both the donor and acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of mid-bandgap polymers and [6,6]-phenyl-C 71 -butyric acid methyl ester (PC 70 BM) is widely studied active layer components, which match the indoor light illuminance mostly lying in the visible wavelength region between 400 and 700 nm. [8][9][10] By contrast, state-of-the-art nonfullerene acceptors have received only minor consideration until recently. This is because their bandgap (E g ) values are relatively small to match the indoor light spectrum, whereas such low E g materials play critical roles in securing the harvest of broadband photons under solar irradiation.…”
Section: Introductionmentioning
confidence: 99%